Histological and safety evaluation of cockle shell-derived CaCO₃ nanoparticle loaded with doxorubicin in dogs - Abubakar, Danmaigoro (2018)
Detrimental tissue effects are associated with chemotherapeutics, despite research progress in cancer treatments. Difficulties are still encountered with tumour targeting due to cancer structural complexity. Doxorubicin (DOX) is a potent anticancer lacking cell specificity leading to reduction in its efficacy. Meanwhile, increase therapeutic targeting to tumour has been shown to have promising therapeutic effect using nanomedicine. Encapsulation of anticancer within bio-nanomaterial aids in their delivery to cancer tissues, thus, ameliorates off-targeted effects of drugs, which has necessitated the importance of exploring the potency of cockle shell-derived calcium carbonate nanoparticle (CS-CaCO3NP) for DOX delivery safely. Homogenous CSCaCO3NP with sufficient physicochemical properties which exhibits promising potential as targeting nanocarrier is desired for chemotherapy. Stimuli-responsive nanocarriers have received great attention in drug delivery towards aiding better selectivity and specificity of drugs in the plasma circulation. DOX is associated with cardio-hepato-renal toxicity effects which hampered its clinical application. CSCaCO3NP is a biodegradable carrier with considerable potential for DOX targeted delivery. Thus, the aim of this study was to evaluate the safety of CS-CaCO3NP-DOX in dogs. The homogeneity of CS-CaCO3NP was obtained through a top-down approach with the help of a roller mill. The CS-CaCO3NP and CS-CaCO3NP-DOX were characterized for physicochemical properties using Transmission Electron Microscopy, Field Emission Electron Microscopy, Zeta Sizer, X-ray Diffraction, Fourier Transformed infrared, and Brunauer-Emmett-Teller techniques. A dissolution non-Fickian control based release kinetics using dialysis bag was employed to evaluate the release pattern. A bioanalytical methods were developed on High Liquid Pressure Chromatography for pharmacokinetic studies in six dogs, which were equally divided and given free DOX and CS-CaCO3NP-DOX for study, a total of 15 healthy dogs were randomized into 5 groups. The Dogs were subjected to slow intravenous infusion up to 5 doses at every 3 weeks interval with (i) normal saline, (ii) DOX 30 mg/m2, and the experimental groups; CS-CaCO3NP-DOX at (iii) high dose, 50 mg/m2, (iv) clinical dose, 30 mg/m2 and (v) low dose, 20 mg/m2. Physical and clinical examination, radiography, electrocardiography, blood profile, cardiac injury biomarkers, histopathology and ultrastructure were employed to evaluate the toxicity and safety while blood profile, tumour biomarker, tumour size and survival rate were used to evaluate the dogs. A homogenous, spherical, porous pH-responsive CSCaCO3NP was obtained with a mean diameter and zeta potential of 24.9 ± 4.07 nm and -26.1 mV respectively. While a mean diameter and zeta potential of CSCaCO3NP- DOX were 39.4 ± 3.04 nm -34.7 mV, respectively. The energy dispersion X-ray analysis revealed a high proportion of calcium with a spectrum peak on FTIR spectra suggesting no alteration upon incorporation of DOX into CS-CaCO3NP with a higher loading capacity and encapsulation efficiency were recorded. An excellent bioanalytical method with high extraction yield and linearity of 89.87% and 0.997 was discovered. The kinetic release profile in neutral buffer medium had 13.7% of DOX released from CS-CaCO3NP after 96 hours, with about 25% concentration release in weak acid medium, while 52.6% of DOX were release from free-DOX in neutral buffer medium. CS-CaCO3NP-DOX increased half-life and area under the curve, with lower clearance rate as compared to free DOX. The cumulative dose of 150 mg/m2 of free-DOX over 15 weeks revealed significant (p<0.05) changes in clinical, haematological profile, serum biochemical alteration, elevations in the cardiac injury markers and histopathologic changes on tissues as compared to dogs given an equivalent cumulative dose of CS-CaCO3NP-DOX. In addition, dogs given CSCaCO3NP- DOX at cumulative dose below 150 mg/m2 did not show any significance (p>0.05) changes as when compared to those given normal saline. This study also revealed no significant changes in systemic toxicity effects in dogs and thus, confirmed the safety of the repeated dose administration CS-CaCO3NP-DOX (30 mg/m2), which improves the quality of life and efficacy in dogs with non-resectable tumours when given 4-5 doses of CS-CaCO3NP-DOX 30 mg/m2. This finding offers great hope to reduce toxicity in dogs with cancer that might undergoes long-term regiment with DOX. These properties underscore the potential of CS-CaCO3NP in the delivery of DOX as new intelligent composite, giving it a high potential in the delivery of the anticancer in the management of dog with cancers.